2001
DOI: 10.1051/jp4:2001831
|View full text |Cite
|
Sign up to set email alerts
|

Ageing effects in a Cu-Al-Ni shape memory alloy

Abstract: Abstract. Ageing of a Cu-14.3Al-4.lNi (wt.%) shape memory alloy was investigated by resistometry and scanning electron microscopy. Four stages were distinguished in isochronal annealing experiments. Underlying processes were discussed with respect to the changes observed in the particular stages. In the early stages of ageing, annealing of quenched-in vacancies is probably the dominant process; the effect of ordering processes seems to be negligible. A decrease in the hysteresis width precedes a pronounced y 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…The transition curves of the forward and reverse transitions for the Cu-Al-Ni-xTi (x = 0.4, 0.7 and 1.0 mass%) aged at different times and temperatures are illustrated in It was found that with an increase in aging time and temperature, the transition temperatures shift toward high temperatures, which is in agreement with other researchers [20][21][22][23][24]. This shifting is mainly attributed to the type and morphology of the martensitic phase, as well as the presence of the precipitates [25,26].…”
Section: Dsc Analysissupporting
confidence: 87%
“…The transition curves of the forward and reverse transitions for the Cu-Al-Ni-xTi (x = 0.4, 0.7 and 1.0 mass%) aged at different times and temperatures are illustrated in It was found that with an increase in aging time and temperature, the transition temperatures shift toward high temperatures, which is in agreement with other researchers [20][21][22][23][24]. This shifting is mainly attributed to the type and morphology of the martensitic phase, as well as the presence of the precipitates [25,26].…”
Section: Dsc Analysissupporting
confidence: 87%
“…To enhance ductility, additional elements can be alloyed to the base alloys such as Mn, Fe, or Ti. The processes behind the ageing phenomena are well described in the Cu-Al based SMAs [1][2][3][4][5][6][7]. These processes include the ordering transitions of the parent β phase and the formation of the equilibrium γ2 and α phases.…”
Section: Introductionmentioning
confidence: 99%
“…Because transformation temperatures are very sensitive on the concentration change, transformation temperatures shift due to the precipitation processes. In addition, if the composition of the matrix is strongly modified, the ability of thermoelastic transformation is destroyed [1,5,6,7,8]. Today's most widely shape memory alloys are NiTi alloys.…”
Section: Introductionmentioning
confidence: 99%